1995
DOI: 10.1002/ffj.2730100506
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of the essential oils of chemotypes of Pimenta racemosa var. racemosa (P. Miller) J. W. Moore (Bois d'Inde) of Guadeloupe (F.W.I.)

Abstract: In Guadeloupe, three kinds of plants that have the botanical name of Pimenta racemosa var. racemosa (P.Miller) J. W. Moore (Myrtaceae) can be found. They differ from one another by the smell of their leaves: smells similar to those of clove, lemon and anise. An analysis of the essential oils of each type shows differences concerning their physical characteristics and their chemical compositions ; in two chemotypes, major amounts of phenolic ethers (eugenol, chavicol, estragole, methyleugenol) were observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 1 publication
1
17
0
4
Order By: Relevance
“…Depending on location, date of the wood harvest, and the length of storage the yield of sulfate turpentine is 6-16 kg t À1 of pulp for a pine, about 2 kg t À1 for a spruce, and 2-3 kg t À1 for a fir. [35] The Field wormwood [22] 11.2 Bay leaf, type "anise" [23] 12.8 Bay leaf, type "clove" [23] 6.4 Ylang-ylang fruit [24] 24.7 Carrot leaf [25] 7.5 Wild thyme [26] 39.1 Jambu flower [27] 11.8 Juniper berry [28] 11.0 Juniper needle [29] 5.5 Lemongrass [30] 10.3 Leaf oil from Zanthoxylum ovalifolium [31] 19.8…”
Section: Turpentinementioning
confidence: 99%
“…Depending on location, date of the wood harvest, and the length of storage the yield of sulfate turpentine is 6-16 kg t À1 of pulp for a pine, about 2 kg t À1 for a spruce, and 2-3 kg t À1 for a fir. [35] The Field wormwood [22] 11.2 Bay leaf, type "anise" [23] 12.8 Bay leaf, type "clove" [23] 6.4 Ylang-ylang fruit [24] 24.7 Carrot leaf [25] 7.5 Wild thyme [26] 39.1 Jambu flower [27] 11.8 Juniper berry [28] 11.0 Juniper needle [29] 5.5 Lemongrass [30] 10.3 Leaf oil from Zanthoxylum ovalifolium [31] 19.8…”
Section: Turpentinementioning
confidence: 99%
“…Porém outros metabólitos secundários também têm sido descritos, tais como, saponinas, flavonóides e taninos (Tabela 1 A composição química dos óleos essenciais contribui significativamente para a determinação do potencial farmacológico atribuído às espécies vegetais e pode sofrer variações em consequência de fatores extrínsecos à biologia vegetal (ambientais ou edáficos) e/ou intrínsecos à biologia vegetal (fisiológicos e genéticos) (Cunha et al, 2005;Simões & Spitzer, 2004). Nesse sentido, foi possível verificar diferença na abundância relativa dos componentes do óleo essencial em folhas de P. dioica macho e P. dioica fêmea em estudo realizado por Minott & Brown (2007 (Abaul et al, 1995).…”
Section: Metabólitos Secundários Identificados E Isolados De Espéciesunclassified
“…Esta atividade foi também atribuída ao alto conteúdo de eugenol presente no óleo essencial do fruto (Bara & Vanetti, 1997/1998 (Oussalah et al, 2006;. O extrato aquoso dos frutos de P. dioica demonstrou atividade antibacteriana para S. aureus (Romero et al, 2005).…”
Section: Pimenta Dioicaunclassified
See 1 more Smart Citation
“…P. racemosa var. racemosa produced three chemotypes with different physical characteristics and chemical compositions (Abaul and Bourgeois 1995). Aurore et al (1998) reported differences in the antimicrobial activities of the three chemotypes of P. racemosa var.…”
mentioning
confidence: 99%